(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2024)
Background: Among the major noncommunicable diseases (NCDs), morbidity and mortality from Diabetes makes the largest contribution worldwide. As a disease, Diabetes Mellitus (DM) is not only a public health threat by itself but also troublesome in concomitant comorbid psychiatric conditions. Objective: To assess the psychiatric morbidity in terms of anxiety and depression among the Type 2 diabetes Mellitus (T2DM) patients. Methods: It was a cross-sectional study conducted among purposively selected 184 previously diagnosed T2DM patients from January 2023 to April 2023 attending at the outpatient department (OPD) of Combined Military Hospital (CMH) Ghatail. Face-to-face interview was done for the collection of data using pretested semi-structured questionnaire. Results: Anxiety was revealed among the respondents significantly (p<0.05) more likely from married, retired and homemaker, monthly income between 7001-20000 taka, reside in a semi-pucca house, duration of diabetes >8 years and having symptoms of diabetes during diagnosis. Depressed respondents were significantly (p<0.05) more likely from age group between 45-55 and >56 years, married respondents, having monthly income between 70001-20000, being with nuclear family, residing in kancha house, age of onset of DM is >46 years with duration of DM >8 years and having symptoms of DM during diagnosis. Conclusion: The study revealed that the relatively higher magnitude of depression and anxiety were found among the T2DM patients reported to the out-patient department of CMH Ghatail. JAFMC Bangladesh, Vol 20, No 1 (June) 2024: 7-13